Cloud object analysis of CERES Aqua observations of tropical and subtropical cloud regimes: Evolution of cloud object size distributions during the Madden–Julian Oscillation. (February 2017) - Xu, Kuan-Man; Wong, Takmeng; Dong, Shengtao; Chen, Feng; Kato, Seiji; Taylor, Patrick C.
Abstract: In this study, we analyze cloud object data from the Aqua satellite between July 2006 and June 2010 that are matched with the real-time multivariate Madden–Julian Oscillation (MJO) index to examine the impact of MJO evolution on the evolutions of the size distributions of cloud object types. These types include deep convective (DC), cirrostratus, shallow cumulus, stratocumulus and overcast-stratus. A cloud object is a contiguous region of the earth with a single dominant cloud-system type. It is found that the cloud object size distributions of some phases depart greatly from the 8-phase combined distribution at large cloud-object diameters. The large-size group of cloud objects contributes to most of the temporal variations during the MJO evolution. For deep convective and cirrostratus cloud objects, there is a monotonic increase in both the number and footprint of large objects from the depressed to mature phases, which is attributed to the development and maturing of deep convection and anvils. The largest increase in the mean diameter during the mature phases that lasts to the early dissipating phase is related to growth of anvil clouds and is accompanied by moderate decreases in small-size objects. For shallow cumulus, the large objects decrease in number at the mature phases, but increase in number for both sizes before the mature phase. The opposite is true for the large overcast-stratus objects. The temporal evolution of large stratocumulus objects is similar to that of deep convective and cirrostratus object types except for peaking slightly earlier. Highlights: Examine the impact of MJO evolution on the evolutions of cloud size distributions. Found that cloud size distributions vary greatly at large diameters during the MJO. Deep convective and cirrostratus cloud objects evolve with MJO with phase delays. Shallow cumulus and overcast-stratus objects evolve in nearly opposite phases. Stratocumulus are similar to deep convective and cirrostratus but peak earlier.